Human C1q Induces Apoptosis in an Ovarian Cancer Cell Line via Tumor Necrosis Factor Pathway - Kaur, Anuvinder; Sultan, Sami H. A.; Murugaiah, Valarmathy; Pathan, Ansar A.; Alhamlan, Fatimah S.; Karteris, Emmanouil; Kishore, Uday (Frontiers in Immunology, 2016)
Complement protein C1q is the first recognition subcomponent of the complement classical pathway that plays a vital role in the clearance of immune complexes, pathogens and apoptotic cells. C1q also has a homeostatic role involving immune and non-immune cells; these functions not necessarily involve complement activation. Recently, C1q has been shown to be expressed locally in the microenvironment of a range of human malignant tumours, where it can promote cancer cell adhesion, migration and proliferation, without involving complement activation. C1q has been shown to be present in the ascitic fluid formed during ovarian cancers. In this study, we have examined the effects of human C1q and its globular domain on an ovarian cancer cell line, SKOV3. We show that C1q and the recombinant globular modules induce apoptosis in SKOV3 cells in a dose-and time-dependent manner. C1q expression was not detectable in the SKOV3 cells. Exogenous treatment with C1q and globular heads at the concentration of 10 μg/ml induced apoptosis in approximately 55% cells, as revealed by immunofluorescence microscopy and FACS. The qPCR and caspase analysis suggested that C1q and globular head modules activated TNF-α and upregulation of Fas. The genes of mTOR, RICTOR and RAPTOR survival pathways, which are often over-expressed in majority of the cancers, were significantly downregulated within few hours of the treatment of C1q and globular head modules. In conclusion, C1q, via its globular domain, induced apoptosis in an ovarian cancer cell line, SKOV3 via TNF-α induced apoptosis pathway involving upregulation of Bax and Fas. This study highlights a potentially protective role of C1q in certain cancers.